2012
DOI: 10.1097/pcc.0b013e318238b07a
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and tolerability of early initiation of noninvasive positive pressure ventilation in pediatric patients admitted with status asthmaticus

Abstract: Early initiation of noninvasive positive pressure ventilation, along with short acting β-agonists and systemic steroids, can be safe, well-tolerated, and effective in the management of children with status asthmaticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 23 publications
0
47
0
14
Order By: Relevance
“…Clinical improvement observed with NHF in the present study was similar to that previously reported with NIV in children [7], and no patient was intubated. However, although the use of NIV for status asthmaticus in children [6, 7, 9, 44, 45] is common, the level of evidence remains limited [10]. Furthermore, in adults, the Cochrane review published in 2012 found that NIV did not provide additional benefit to medical treatment [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical improvement observed with NHF in the present study was similar to that previously reported with NIV in children [7], and no patient was intubated. However, although the use of NIV for status asthmaticus in children [6, 7, 9, 44, 45] is common, the level of evidence remains limited [10]. Furthermore, in adults, the Cochrane review published in 2012 found that NIV did not provide additional benefit to medical treatment [46].…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental oxygen is commonly administered to children with an asthma exacerbation in the emergency department or intensive care unit in association with beta 2 agonist nebulization [35]. Non-invasive ventilation (NIV) may be used as respiratory support in children with status asthmaticus in case of standard treatment failure [69]. However, the level of evidence of its efficacy remains low according to the grade system of evidence quality [10].…”
Section: Introductionmentioning
confidence: 99%
“…1 NIV is associated with improved mortality in adult patients with COPD and other forms of respiratory distress. [2][3][4][5][6][7][8][9][10][11][12] One randomized controlled trial 13 and several small observational studies [14][15][16] found NIV safe and effective in supporting children with respiratory failure, including patients with asthma not responding to conventional therapies.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all studies adjusted for confounding factors, and the lack of multicenter involvement prevents widespread generalizability of their findings. Findings from the few RCTs available on this topic in critically ill children do support the premise of improved outcomes for selected patients treated with NIV in preference to IV (710). …”
Section: Discussionmentioning
confidence: 91%
“…Randomized controlled trials (RCTs) in adults with chronic obstructive pulmonary disease and cardiogenic pulmonary edema, and in premature newborns with respiratory distress, have demonstrated that noninvasive ventilation (NIV) modalities such as continuous or bi-level positive airway pressure can reduce the need for endotracheal intubation and improve patient outcomes (26). However, there is a paucity of RCT evidence in critically ill children: just one clinical trial including only 50 patients, and three other small RCTs restricted to specific conditions such as bronchiolitis, asthma, and dengue shock syndrome exist (710). Despite this scarcity of evidence, national audit data from PICUs in the United Kingdom and Ireland have shown increasing use of NIV over the past 10 years (11), mirroring an international trend of greater adoption of NIV (12, 13).…”
mentioning
confidence: 99%